2015
DOI: 10.2131/jts.40.309
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid and growth hormone concentrations in 8-year-old children exposed <i>in utero</i> to dioxins and polychlorinated biphenyls

Abstract: -The objective of this study was to examine the effects of in utero exposure to polychlorinated biphenyls (PCBs) and dioxins (polychlorinated dibenzo-p-dioxins, dibenzofurans (PCDD/F) on thyroid and growth hormone concentrations and growth in 8-year-old children. A total of 56 children (23 boys, 33 girls) were included in the study. All were stratified into high and low PCDD/F + PCB exposure groups based on maternal median indicator PCB and PCDD/F + PCB concentrations during pregnancy. Height, weight, body mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Su et al. () compared levels of thyroid hormones (TSH, T4, free T4, T3) in 56 eight‐year old children with PCDD/F‐PCB‐TEQs above or below the median, which was 14.8 pg/g fat. No adjustment for potential confounders was applied and no significant differences were found.…”
Section: Assessmentmentioning
confidence: 99%
“…Su et al. () compared levels of thyroid hormones (TSH, T4, free T4, T3) in 56 eight‐year old children with PCDD/F‐PCB‐TEQs above or below the median, which was 14.8 pg/g fat. No adjustment for potential confounders was applied and no significant differences were found.…”
Section: Assessmentmentioning
confidence: 99%
“…The majority of longitudinal studies have not observed associations between prenatal nor lactational NDL-PCB concentrations and childhood BMI or other measures of adiposity (Criswell et al 2017;Dallaire et al 2014;de Cock et al 2014;Hertz-Picciotto et al 2005;Jackson et al 2010;Karlsen et al 2017;Lauritzen et al 2018;Mendez et al 2011;Pan et al 2010;Patandin et al 1998;Su et al 2015;Vafeiadi et al 2015;Valvi et al 2014). Prenatal NDL-PCBs, however, were associated with higher BMI among both boys and girls in Belgium (Verhulst et al 2009) and Spain (Agay-Shay et al 2015;Valvi et al 2012) at ages 3 and 6.5-7 years, respectively, although the association was attenuated in the Belgian study by age 7-9 years (Delvaux et al 2014).…”
Section: Discussionmentioning
confidence: 88%
“…In early pregnancy, the fetal thyroid hormone is completely dependent on transport from the mother prior to fetal self-synthesis (113). An increasing number of epidemiological studies have confirmed that gestational PcB exposure was associated with disturbances in the thyroid function of neonates (114)(115)(116). This destruction has long-lasting effects in the offspring, potentially lasting until the child is 8 years old (116).…”
Section: Dl-and Ndl-pcbs Alter Genetic and Epigenetic Informationmentioning
confidence: 99%
“…An increasing number of epidemiological studies have confirmed that gestational PcB exposure was associated with disturbances in the thyroid function of neonates (114)(115)(116). This destruction has long-lasting effects in the offspring, potentially lasting until the child is 8 years old (116). The effects of PcBs and OH-PcBs on thyroid function may involve the following mechanisms: i) PcBs may competitively bind to transthyretin, particularly OH-PcBs, which have stronger binding affinity compared with that in their parent compounds; ii) PcBs may interact with thyroxine receptors or suppress dNA transcription and iii) OH-PcBs inhibit thyroid hormone sulfation, affecting the peripheral metabolism of thyroid hormones (114,117).…”
Section: Dl-and Ndl-pcbs Alter Genetic and Epigenetic Informationmentioning
confidence: 99%